RECONSTRUCTING THE EDUCATIONAL MEANING OF FARĀGH IN THE PROPHETIC HADITH: A QUALITATIVE THEMATIC STUDY AND ITS IMPLICATIONS FOR ISLAMIC RELIGIOUS EDUCATION - Ridwan, Ridwan; Rahayu, Putriyana; Juariah, Nani (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study is motivated by the tendency to perceive leisure time (farāgh) in education merely as a break without value orientation, even though empirical studies show that most students spend free time on non-academic activities with minimal educational benefit, such as using gadgets, sleeping, or casual conversations. This article aims to reconstruct the educational meaning of farāgh in the Prophet’s ﷺ traditions (hadith) and its implications for Islamic Religious Education (PAI). A qualitative approach was used through digital library research with a thematic (maudhū‘ī) method applied to authentic hadiths concerning time, deeds, and responsibility. Primary data were obtained from the Al-Bāhits Al-Hadītsī application, and secondary data from peer-reviewed journals, syarh literature, and Islamic education references. Analysis was descriptive-analytical and normative-conceptual using source triangulation among hadith texts, classical commentaries, and contemporary educational theories. Findings indicate four dimensions of farāgh: (1) a divine trust (amānah) for which humans are accountable; (2) a momentum for righteous deeds before life’s obstacles arise; (3) eschatological awareness to be reckoned with in the Hereafter; and (4) a foundation for productivity and beneficial action. Three pedagogical principles emerge: spiritual self-regulation, meaningful productivity, and eschatological consciousness. Farāgh offers a more comprehensive framework than modern time management as it integrates spiritual, moral, and transcendental dimensions. In conclusion, farāgh is not merely leisure but a strategic instrument for cultivating religious character, discipline, and moral responsibility in PAI, expanding education from cognitive transmission toward a time-management habitus oriented toward both worldly life and the Hereafter.